Against all odds: The role of ‘community cultural wealth’ in overcoming challenges as a black African woman - Nkambule, Thabisile (Unisa, 2014)
Academic challenges for students from ‘previously disadvantaged backgrounds’ do not necessarily begin at university, but start during their school years, as was the case for the author. This article is in three parts. Firstly, the author presents a brief narration of the challenges faced before she went to university, which influenced her undergraduate progress. Secondly, the author describes the key challenges she experienced as an undergraduate in particular courses and in a postgraduate education course. Thirdly, she focuses on the challenges she encountered during her first work experience as a black African PhD student and tutor on an education campus. In particular, the author focuses on key challenging incidents and how she approached and engaged with them to enable a successful journey through university as a student and young academic staff member. In the form of a first-person narration, the qualitative research method of ‘testimony’ is used to reflect critically on her academic and professional journeys as a black African woman in the post-apartheid era. Testimony was chosen because it provides an epistemic lens to support an analytical inquiry into experiences and intellectual understanding of self and community.
Keywords: Community cultural wealth – South Africa; Black African women – higher education – South Africa